Design and development of a system for analysis of movement of the hand and wrist - Gutiérrez - Martínez, J.; González - Leyva, A.; Ortiz - Espinosa, A.; Núñez - Gaona, M. A.; Barraza - López, E. F.; Piña - Ramírez, O. (Revista Mexicana de Ingenieria Biomedica, 2011)
Range of motion of the joint of the hand is necessary to do a quantitative functional evaluation. Mechanical goniometry is the typical procedure to measure finger joints, but this method has several problems; instrument, subjective examiner-dependent, tedious and high time consuming. In this paper, we present the design of a 2D-images prototype video-based movement analysis system to measure the joint of the hand and wrist in space including three perspectives. The instrumentation is centered on glove with markers, each placed on proximal and distal phalanges of the fingers and also the wrist. Hand images are acquired using three digital cameras, a card video and they are processed with Vision Builder. The GUI was designed in Lab-VIEW platform and its specifications get clinical requirements. The examiner may make quantitative, easy and trustworthy evaluation kinematic of the hand. He can take reliable values because they are between literature ranges. Then, he can do his treatment, surgical and rehabilitation decisions in an objective way. The video-based system to measure the hand’s joints represents a good tool to substitute the manual goniometer.